1981
DOI: 10.1111/j.1600-0528.1981.tb01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene habits among adolescents in Finland

Abstract: The aim of this study was to analyze oral hygiene habits among Finnish adolescents with regard to age, sex, residence, socioeconomic factors, school career and success. A representative sample of 3209 Finnish adolescents, 13-19 years of age, was drawn. The data were collected by mail surveys in February and September 1977. Participation percentages were 88 and 79. The proportions of daily brushers were 89% in girls and 57% in boys. Toothpicks were used sporadically by every second adolescent but daily by 3% on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…A European health survey of adolescents revealed that positive school experience is strongly associated with better self-rated general health and life satisfaction, few health complaints, and a low risk of smoking and alcohol use [21]. Moreover, school performance is consistently associated with oral health behavior, especially toothbrushing, consumption of soft drinks, and sweets [20,26,27], and the present study in China supports the European observations. The Chinese adolescents who performed well at school were relatively likely to have regular toothbrushing and dental visiting habits.…”
Section: Discussionsupporting
confidence: 90%
“…A European health survey of adolescents revealed that positive school experience is strongly associated with better self-rated general health and life satisfaction, few health complaints, and a low risk of smoking and alcohol use [21]. Moreover, school performance is consistently associated with oral health behavior, especially toothbrushing, consumption of soft drinks, and sweets [20,26,27], and the present study in China supports the European observations. The Chinese adolescents who performed well at school were relatively likely to have regular toothbrushing and dental visiting habits.…”
Section: Discussionsupporting
confidence: 90%
“…School performance was also consistently associated with toothbrushing in all countries except Latvia and Belgium. This association has also been observed in earlier studies (Honkala et al, 1981;Traeen and Rise, 1990). Better school performance could, to some extent, predict better socio-economic status in the future and therefore may be considered as just another ods to affect the children of disadvantaged groups.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, family economy was a subjective measure-the child's own perception of the family economy. However, it could be expected to measure family economy quite reliably, and several other epidemiological surveys have also shown the importance of socio-economic background for determining children's toothbrushing behavior (Honkala et al, 1981;Macgregor and Balding, 1987;Bedi et al, 1990;Addy et al, 1994). School performance was also consistently associated with toothbrushing in all countries except Latvia and Belgium.…”
Section: Discussionmentioning
confidence: 93%
“…Koivusilta et al [22] and Honkala et al [23] reported that tooth brushing habits improved as the level of education increased. Although not statistically significant, there was a positive correlation between tooth brushing habits and level of education in the present study's patient group.…”
Section: Discussionmentioning
confidence: 99%